ATM kinase inhibitor KU-55933 contribution in cisplatin mediated HeLa proliferation - Bhatkar, Devyani; Kumar, Ajay; Jahagirdar, Devashree; Purohit, Shruti; Sharma, Nilesh Kumar (International Journal of Pharmacology and Toxicology, 2016)
Several approaches including chemotherapy and radiation therapies are being at the forefront to treat various types of cancer including cervical cancer. However, the success and failure of genotoxic based therapy is attributed to aberrant ability of carcinoma to patch up genomic breaks. Here, we have used cisplatin as a genotoxic drug model and HeLa as in vitro carcinoma model due to less responsiveness and resistance of HeLa against cisplatin. Here, attempts are made to investigate the effects of DNA double strand break inhibitor KU-55933 against the cisplatin cell growth and cytotoxicity. Following experiments namely in vitro plasmid DNA metabolizing, Trypan blue dye exclusion, MTT, and PI based Flow cytometery PI assays were conducted to study cell growth and cytotoxicity effects. Based on the cell viability and PI based staining data, results remarked that KU-55933 combined with cisplatin could bring convincing cell growth arrest in HeLa. The reduction in HeLa proliferation was noticed from 70% to 30% in case of KU-55933 added with cisplatin over cisplatin alone. However, we noticed none apoptosis based cell cytotoxicity in case of cisplatin alone or combined with the inhibitors. We also observed significant DNA instability in case of KU-55933 treated HeLa lysates added to plasmid DNA substrate over HeLa lysate without KU-55933 treatment. In conclusion, KU-55933 can potentiate low dose of cisplatin response against HeLa. The effect of KU-55933 may not be attributed due to its enhancing the apoptosis way, rather than through cell growth arrest mechanism due to extensive DNA breaks.